Preclinical and clinical trials for vaccine induction of CD4-binding site-neutralizing antibodies - Catarina Mendes Silva; Rogier W. Sanders; Tom G. Caniels (Current Opinion in HIV and AIDS, 2026)
Purpose of review To summarize current preclinical and clinical efforts to induce CD4bs-directed broadly neutralizing antibodies (bnAbs) against HIV-1 Env using germline-targeting and lineage-based vaccination strategies, and to highlight how differences in immunogen design, particularly along gradients of precursor affinity and structural constraint, shape VRC01-class responses and inform subsequent shaping and polishing steps in vaccine regimens. Recent findings Phase 1 trials of CD4bs-directed germline-targeting immunogens have shown that VRC01-class precursors can be reproducibly expanded in humans. Smaller gp120-based immunogens exhibit higher precursor affinity and recruit larger, more diverse VRC01-class pools, whereas native-like trimers prime fewer lineages but drive more on-track somatic hypermutation, early glycan accommodation, and neutralization of heterologous viruses. In parallel, preclinical work is centred around the selection of shaping and polishing immunogens, alternative dosing strategies, and controlled-release or mRNA-LNP platforms to extend maturation. Summary With proof-of-concept for VRC01-class priming being achieved, the next challenge is to induce strong serum antibodies and memory B cells with breadth and potency. Progress toward a protective CD4bs-directed HIV-1 vaccine will require further optimization of adjuvants, delivery systems, and sequential immunogen design to balance precursor recruitment with structural constraint and to sustain affinity maturation across multidose regimens, ultimately driving rare lineages to durable bnAb responses in diverse populations.